Absence of N-Acetylglucosamine Glycosylation on Listeria monocytogenes Wall Teichoic Acids Promotes Fatty Acid Tolerance by Repulsion From the Bacterial Surface - Thomasen, Rikke S. S.; dos Santos, Patricia T.; Sternkopf Lillebæk, Eva M.; Skov, Marianne N.; Kemp, Michael; Kallipolitis, Birgitte H. (Frontiers in Microbiology, 2022)
Free fatty acids (FFAs) have strong antimicrobial properties against pathogenic bacteria and are known as natural protective agents against bacterial infections. Growth of the foodborne pathogen Listeria monocytogenes is highly affected by the presence of antimicrobial FFAs, however, the response of L. monocytogenes towards FFAs is not fully understood. Here, we explore how L. monocytogenes gains tolerance towards FFAs and present a novel mechanism conferring bacterial protection against FFA toxicity. Strains tolerant against the antimicrobial FFA palmitoleic acid were isolated and whole genome sequenced, and mutations were found in genes involved in wall teichoic acid (WTA) glycosylations. We show that mutation or deletion of lmo1079, which is essential for N-acetylglucosamine (GlcNAc) glycosylation of WTAs, confer tolerance against several antimicrobial FFAs. The FFA tolerant strains are lacking GlcNAc on their WTAs, which result in a more hydrophilic surface. In line with this, we observed a reduced binding of FFAs to the surface of the FFA tolerant strains. Additionally, lack of GlcNAc on WTAs confers tolerance towards acid stress. Altogether, these findings support that GlcNAc modification of WTA plays an important role in the response of L. monocytogenes towards stress conditions encountered during growth as a saprophyte and pathogen, including FFA-rich environments. Most importantly, our data revealed that L. monocytogenes strains lacking GlcNAc on their WTAs are protected against FFA toxicity, because the FFAs are repulsed from the bacterial surface of GlcNAc-deficient strains.